Os traços depressivos na histeria feminina: um olhar psicanalítico - Gori, Cláudia Andréa (2010)
This study is a psychoanalytic view of Maria Callas biographic fragments, the greek origin soprano. It aims to reveal the facilitator power of the libido fixation on the oral phase, in the manifestation of depressive signs that are present in the hysteric organization of this lyric artist. The study of the depressive aspects in the feminine hysteria was realized from a course through Maria Callas biographic fragments, which I selected and extracted from her biography written by Arianna Stassinopoulos Huffington, called Maria Callas. The Woman Behind the Myth. This research has its basis in the psychoanalysis, regarding the theory about the psychism constitution and functioning. Its grantee representatives are Sigmund Freud and Piera Aulagnier. In this research, I do as Freud did in relation to the analysis of the first manuscript of Mariazell sanctuary, called Trophaeum Mariano-Cellense, which has a detailed description about Christoph Haizmann s demonological neurosis, a Bavarian painter from the XVII century. I also guide myself by Freud s steps suggested in one of his text written in 1937, called Constructions in Analysis , and rely on Maria Callas biographic data by a fluctuant act of reading and listening, that operates through a suspension of everything that the attention regularly focuses on, opening the access paths to the supposed unconscious thoughts and to the supposed subject s libidinal and identifying history. Thus, based on the clinics and the theory of the authors above mentioned, I conceive the thesis according to the following in the supposed Maria Callas libidinal and identifying history, the libido fixation on the oral phase that may be established due to the lack of maternal libidinal investment, in a prevalent way -, which can be a facilitator factor to the manifestation of the depressive sign in its possible hysterical psychic constituition